Answer

Verified

414.3k+ views

**Hint:**Arithmetic progression (AP) or arithmetic sequence is a sequence of numbers such that the difference between the consecutive terms is constant.

Difference here means the second minus the first term.

If the initial term of an arithmetic progression is \[{a_1}\]and the common difference of successive members is d them the \[{n^{th}}\] term of the sequence \[{a_n}\] is given by

\[{a_n} = {a_1} + (n - 1)d\]

The behaviour of the AP depends on the common difference d. If the common difference is

\[ \to \]Positive, then the terms will grow towards positive infinity.

\[ \to \] Negative, then the term will grow towards negative infinity.

Now, In the formula

\[{a_n} = {a_1} + (n - 1)d\]

\[ \to {a_1}\] is the first term of an AP

\[ \to \] \[{a_n}\] is the \[{n^{th}}\] term of an AP

\[ \to \] d is the difference between terms of the AP

\[ \to \] n is the number of terms in the AP.

**Complete step-by-step answer:**

Given AP is

\[7,13,19,....205\]

Using the formula

\[{a_n} = a + (n - 1)d\]

Here, first term of AP is

\[a = 7\]

To find the value of $d$ we need to subtract the second term from first term.

\[d = (Second\,term - First\,term)\]

\[d = 13 - 7 = 6\]

Last term is \[an = 205\]

Now, find A.P.

\[{a_n} = a(n - 1)d\]

Put values of each,

We get,

\[\begin{gathered}

205 = 7 + (n - 1) \times 6 \\

205 - 7 = (n - 1) \times 6 \\

198 = (n - 1) \times 6 \\

\end{gathered} \]

Simplify

\[\begin{gathered}

\dfrac{{198}}{6} = n - 1 \\

33 = n - 1 \\

33 + 1 = n \\

34 = n \\

\end{gathered} \]

We have,

$n = 34$

Hence there are 34 terms in the given AP.

**Note:**The sum of the members of finite AP is called on arithmetic series.

For example, consider the sum:

\[2 + 5 + 8 + 11 + 14\]

This sum can be found quickly by taking the number ‘n’ of term bring added (here 5), Multiplying by the sum of the first and last number in the progression and dividing by 2.

\[\begin{gathered}

\dfrac{{n({a_1} + {a_n})}}{2}\,\,\, \\

n = 5 \\

{a_1} = 2 \\

an = 14 \\

\end{gathered} \]

In the case above, this gives the equation

\[2 + 5 + 8 + 11 + 14 = \dfrac{{5(2 + 14)}}{2} = 40\]

Recently Updated Pages

Differentiate between Shortterm and Longterm adapt class 1 biology CBSE

How do you find slope point slope slope intercept standard class 12 maths CBSE

How do you find B1 We know that B2B+2I3 class 12 maths CBSE

How do you integrate int dfracxsqrt x2 + 9 dx class 12 maths CBSE

How do you integrate int left dfracx2 1x + 1 right class 12 maths CBSE

How do you find the critical points of yx2sin x on class 12 maths CBSE

Trending doubts

Give 10 examples for herbs , shrubs , climbers , creepers

Difference Between Plant Cell and Animal Cell

Name 10 Living and Non living things class 9 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

List some examples of Rabi and Kharif crops class 8 biology CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE